Bortezomib for the treatment of previously untreated multiple myeloma. (April 2013) - Romano, Alessandra; Conticello, Concetta; Di Raimondo, Francesco
Management of multiple myeloma (MM) has been drastically changed in the last 10 years thanks to the introduction of novel agents, which, combined with the backbone of classical chemotherapy, have led to a significant improvement in disease control. Bortezomib is the first reversible proteasome inhibitor approved for the treatment of MM, with wide synergism in vitro and in vivo with a plethora of drugs active for MM. In patients eligible for autologous stem cell transplantation (ASCT), the achievement of complete response or very good partial response before ASCT is associated with prolonged progression-free and overall survival. Thus, the goal of induction regimens should include, at least for younger patients, a continued improvement of the quality and depth of the achieved response. This article is focused on reviewing the major efforts in frontline therapy for MM, including bortezomib-containing induction regimens in patients either eligible or ineligible for ASCT.